Kajian Hubungan Kuantitatif Struktur Dan Aktivitas (HKSA) Senyawa Kurkumin Dan Turunannya Sebagai Agen Anti Tumor Darah Terhadap Penghambatan Pertumbuhan Sel K562 - Puspitasari, Ismi; Astuti, Sari; Harmastuti, Nuraini (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Curcumin was reported can suppress the growth of blood tumor cells. This study aims to determine the physical and chemical properties of curcumin derivatives that give affect to antitumor activity of blood cells which were expressed as the best HKSA equation model. This study used curcumin and twelve derivatives which have antitumor activity parameters of blood cells (K562) as IC50. Parameters of physicochemical properties of curcumin compounds series and their derivatives as descriptors include net charge of atoms in the curcumin framework structure, EHOMO, ELUMO, Log P, E Hid, a, MR, Volume, Surface area (SA), Total Energy, dipole moment (u), Hf, and Mass which are the results of geometric optimization calculations using the PM3 semiempirical method with hyperchem application. HKSA equation model was built using the BuilQSAR statistical calculation analysis. The best HKSA equation model is then validated internally and externally. Calculation of statistical analysis with BuldQSAR, the descriptor that has the most influence is obtained, namely net atomic charge, EHOMO, surface area, dipole moment and Hf with linear regression equation: Log 1/IC50 : + 1.7622 (± 0.3655) qC4 - 0.9457 (± 0.1047) E Homo + 0.0013 (0.0002) SA + 0.0575 (± 0.0216) u - 0.0068 (± 0.0004) Hf - 11.4161 (± 1.0440) , n = 10; R = 0.999; R2= 0,9990; SPress = 0.0232. as well as non-linear regression equation : Log 1/IC50 = + 15.1400 (±4.9008) qC7 + 7.4959 (± 5.6081) qC8 - 0.5839 (± 0.1397) qC15 + 0.0005 (± 0.0003) SA - 0.0054 (±0.0008) Hf - 5.7246 (±3.2476), n = 10; R = 0,999, R2 = 0,9977; SPress = 0.0341.